Review of recent researches on air pollution effects on human cognitive functions - Talaeizadeh, Ziba; Zaeimdar, Mozhgan; Kashefi Alasl, Morteza; Marandi, Reza; Ali Jozi, Seyyed (International Journal of Engineering and Technology, 2018)
Air pollution is of factors leading to disturbance in nervous system while its acute neurological effects have not been completely studied. In metropolis, communities experience various social problems caused by air pollution such as retardate, academic disability, and increasing crime rate due to disturbed cognitive functions of children and vulnerable generation without being aware of the effect of air pollution on perception power of human. In this research, the published researches in 2017 available in database and publishers of valid scientific publications such as PubMed and Elsevier were reviewed then 11 related papers were selected to check and criticize their methodology, research instruments and results. Results indicated that the review researches employed various tests and instruments to assess cognitive functions, but most of them obtained similar results introducing disturbing and preventive effect of air pollution on mental functions; however, these studies did not determine the prominent effect of each air pollutant factor on specific area of brain and effect of genetic and environmental background of individuals. Moreover, valid and authentic tests were not employed in many of these papers to assess cognitive function and perception power, while validity and reliability of each of cognitive function tests have been determined and proved to assess the function of specific part of brain.